Integração interdisciplinar na educação científica e matemática na formação do pedagogo - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
This research aims to critically investigate the scientific and mathematical education of pedagogues in training at the Federal University of Western Pará (UFOPA), through the application of virtual questionnaires, which sought to evaluate the perception of future pedagogues in relation to scientific and mathematical skills.The work presents a structure organized into chapters, the first deals with Scientific and Mathematics Education in general, considering the perspective of different authors, the second explores the importance of Scientific Education in the training of the pedagogue and ends with a subchapter that addresses the existing gap in the training of pedagogues in relation to these themes, aligning with social demands for greater integration between education and science. With practical suggestions for overcoming identified flaws. The methodology used is a mixed approach that integrates bibliographical research covering previous studies involving this perspective and empirical research that consists of a discursive textual analysis of the online questionnaire answered by pedagogues in training, analyzed in three stages, as proposed by Moraes and Galiazzi (2006). It is concluded that a review of the course's curricular structure is necessary, given that, since 2015, Scientific and Mathematics Education has not received the necessary emphasis and, when integrated, is not approached in an interdisciplinary way, being restricted to the curricular components of science and mathematics.
Keywords: Educação; Pedagogo; Formação; Integração; CNPQ:: CIÊNCIAS HUMANAS